Mechanistic exploration of the activities of poly(lactic-co-glycolic acid)-loaded nanoparticles of betulinic acid against hepatocellular carcinoma at cellular and molecular levels. (4th May 2022) - Kumar, Pranesh; Gautam, Anurag Kumar; Kumar, Umesh; Bhadauria, Archana S.; Singh, Ashok K.; Kumar, Dinesh; Mahata, Tarun; Maity, Biswanath; Bera, Hriday; Saha, Sudipta
Abstract: The effectiveness of betulinic acid (B) and PLGA loaded nanoparticles of B (Bnp) against hepatocellular carcinoma (HCC) was established and reported earlier. In continuation of our previous report, the present study described the molecular mechanisms of their antineoplastic responses. In this context, the antineoplastic properties of both B and Bnp were evaluated on DEN-induced HCC rat model. The quantitative real-time polymerase chain reaction and western blot analyses revealed that HCC was developed through lower expressions of e-NOS, BAX, BAD, Cyt C and higher expressions of i-NOS, Bcl-xl, Bcl-2. B and Bnp normalised the expressions of these apoptogenic markers. Particularly, both activated i-NOS and e-NOS mediated Bcl-2 family proteins→CytC→Caspase 3 and 9 signalling cascades. The 1 H-NMR-based metabolomics study also demonstrated that the perturbed metabolites in DEN-induced rat serum restored to the normal level following both treatments. Moreover, the antineoplastic potential of Bnp was found to be comparable with the marketed product, 5-flurouracil.